2015
DOI: 10.1111/ene.12715
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in a population‐based study of patients with multiple sclerosis: differences between late relapsing−remitting, secondary progressive and primary progressive multiple sclerosis

Abstract: In this population-based study, patients with a progressive subtype of MS were more frequently and more severely impaired than patients with RRMS, even after more than 10 years of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 24 publications
5
89
3
3
Order By: Relevance
“…At baseline, the most prominent cognitive deficits were in attention and speed of information processing, frontal lobe function, verbal and non-verbal recall, and working memory. This profile is similar to that reported previously in other cross-sectional SPMS groups 2, 22, 23, 24…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…At baseline, the most prominent cognitive deficits were in attention and speed of information processing, frontal lobe function, verbal and non-verbal recall, and working memory. This profile is similar to that reported previously in other cross-sectional SPMS groups 2, 22, 23, 24…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the reproducibility and ease of administration of the FAB confers advantages in terms of application to large multiple sclerosis cohorts. The FAB has previously been used in patients with multiple sclerosis, principally in studies focused on assessment of quality of life and coping strategies, but also as part of an executive function battery 2, 27. To our knowledge, this is the first study to use the FAB as an independently reported cognitive outcome measure within a longitudinal interventional study, and the study findings show the importance of including a comprehensive assessment of frontal lobe function in future multiple sclerosis interventional studies, either as an individual outcome measure or in addition to current batteries such as the Brief International Cognitive Assessment for MS 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cognitive deficits in MS include impairments in learning and memory, verbal fluency and executive functioning (Prakash et al 2008). Cognitive impairment in MS is detectable from the earliest stages of MS and is generally more evident in progressive types such as secondary progressive (SP) MS (Planche et al 2015). Microstructural abnormalities and lesions in white matter significantly disrupt structural and functional connectivity between various brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…The MSFC had rightly highlighted the need for a good and robust measure of cognition in clinical trials as approximately 45-60 % of all MS patients have a cognitive impairment [86,87], and progressive MS patients experience cognitive difficulties more frequently and more severely than RRMS patients [88]. The Rao brief repeatable neuropsychological battery (BRNB) and the minimal assessment of cognitive function in MS (MACFIMS) represent the most used and validated cognitive assessments in MS patients [89].…”
Section: Clinical and Patient-reported Measuresmentioning
confidence: 99%